Safe, Healthy, And Quality Food And Snack Education At State Elementary School 011 Sekupang Batam - Gunawan, Agung Arif; Amalia, Eva; Saputra, Eryd (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
It is important to educate about safe, healthy, and quality food and snacks in the school environment, especially for the generation between the ages of 7-12 years who certainly have a tendency to consume junk food, both snacks in the school environment (canteen) and street food that is widespread in the city of Batam. Elementary school-aged children are a group that is very vulnerable to various health problems related to food and snack consumption. During the growth period, children tend to like snacks that are attractive in color, taste, and shape without paying attention to aspects of cleanliness, safety, and nutritional content. The purpose and message to be conveyed in this Community Service activity include that the role of education is not only to provide intellectual education, but can also pay attention to the health of school students, including the food they consume. Through this activity, teachers and students can share knowledge about food safety, food hygiene, and how to choose and process healthy snacks. This educational activity is expected to be able to shape healthier consumption behavior among elementary school students and encourage the school environment to pay more attention to food safety.